The effectiveness of an electronic stories activities in developing social responsibility skills for kindergarten-aged children - Mubaraki, Reem Abdullah Ahmed; Al-Zahrani, Badriya Dhaifallah (Journal of Curriculum and Teaching Methodology, 2022)
The current research aimed to investigate the effectiveness of electronic narrative activities in developing social responsibility among kindergarten children. To meet such end, the quasi-experimental method was utilized; the research sample consisted of (50) male and female children (level 2) in kindergarten enrolled in primary (212) in the Tuwaiq district in the Riyadh region. The participants were randomly assigned into two groups: a control group and an experimental one. The social responsibility scale (developed by the researcher) was adopted for collecting the research data. The field experiment of the research was carried out via presenting the electronic narrative activities (developed by the researcher) to the experimental group; while the control group studied the usual content via the usual method of teaching. The results of the research revealed that there were statistically significant differences at (α = 0.05) level between the mean scores attained by the experimental and the control one in the post administration of the illustrated social responsibility scale in favor of the experimental group; the effect size of the electronic narrative activities in developing the skills of social responsibility as a whole was large, and the effect size of the electronic narrative activities in developing the dimensions of social responsibility separately, namely: maintaining public morals, cooperation, adherence to regulations and laws participation was also large. In the light of the results attained, the researcher recommended employing narrative activities to provide children with the necessary social responsibility skills among kindergarten children, and raising the efficiency of teachers through training and qualification and the adopting modern methods and means to teach children the methods of social responsibility.
Keywords: Electronic stories Activities; Social Responsibility Skills; Kindergarten Children